PENGARUH FEE AUDIT, TIME BUDGET PRESSURE, DUE PROFESSIONAL CARE, DAN INTEGRITAS AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI BALI - Ni Komang Riskayani; Gde Herry Sugiarto Asana (Universitas Triatma Mulya, 2022)
This study aims to determine the effect of audit fee, time budget pressure, due professional care and auditor integrity on audit quality. This research was conducted at a Public Accounting Firm in Bali registered with the Indonesian Institute of Public Accountants as of January 2021 with a total of 17 Public Accounting Firms. The sampling technique of this study used the porpusive sampling method, so that the research sample used was 70 auditors. The data analysis technique used in the research is descriptive statistic, data quality test, classical assumption test and multiple linear regression analysis with the help os SPSS 25 software for windows. The result of the research on audit fee, time budget pressure, due professional care and auditor integrity have a positive and significant effect on audit quality. The test results of the coefficient of determination (Adjust R Square) of 0,054 which means that 54% of the variables audit fee, time budget pressure, due professional care, and auditor integrity and the remaining 46% are explained by other factors not included in this research model